The Religious Habits Program's Implementation as an Attempt to Mould Students' Islamic Character - Fajri, Zaenol; Hadi, Samsul (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: Developing students' Islamic character is one of the primary objectives of religious-based education, yet religious habituation programs frequently struggle with implementation and consistency. This study examines the implementation of the religious habituation program at Nurul Hikmah Islamic Junior High School and its function in fostering students' Islamic character. Methodology: The principal, homeroom teachers, Islamic education teachers, and a few chosen students served as informants in this descriptive qualitative study. Miles and Huberman's interactive approach, which consists of data reduction, data display, and conclusion drawing, was used to examine the data gathered through documentation, in-depth interviews, and observation. Triangulation of sources and methods was used to guarantee the veracity of the data. Main Findings: The results demonstrate that organised practices, such as communal Dhuha prayer, Qur'anic recitation, group prayers, and disciplinary training, are used to practice religious habituation. These activities effectively uphold religious principles and aid in developing students' character. Limited facilities, the' lack of discipline among confident pupils, and differing parental support are among the difficulties. The school's institutional dedication, an intense religious atmosphere, and faculty involvement are all supporting aspects. Novelty/Originality of this study: The study concludes that Islamic character is effectively shaped by religious habituation. It is innovative in that it maps the characteristics that facilitate and hinder the boarding school setting and provides a contextual approach to enhancing religious culture in Islamic secondary schools.